2010
DOI: 10.1097/gco.0b013e32833e498a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prolapse repair on voiding and bladder overactivity

Abstract: POP repair (surgery/ring pessary) has a positive effect on the resolution of OAB, detrusor overactivity and voiding dysfunction, providing a theory for a causal effect between the conditions. Larger prospective observational studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The cure rate for OAB after non‐mesh POP surgery ranges from 45% to 82% . POP repair also has a positive effect on the resolution of DO and other voiding dysfunctions . In recent years, TVM repair has become one option for improving outcomes of pelvic reconstructive surgery, despite insufficient evidence on the long‐run safety.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The cure rate for OAB after non‐mesh POP surgery ranges from 45% to 82% . POP repair also has a positive effect on the resolution of DO and other voiding dysfunctions . In recent years, TVM repair has become one option for improving outcomes of pelvic reconstructive surgery, despite insufficient evidence on the long‐run safety.…”
Section: Discussionsupporting
confidence: 92%
“…5,8,16,18,23 POP repair also has a positive effect on the resolution of DO and other voiding dysfunctions. 16,18,23,24 In recent years, TVM repair has become one option for improving outcomes of pelvic reconstructive surgery, despite insufficient evidence on the long-run safety. Our results showed that 70% of DO and more than 50% of urgency and urgency incontinence disappeared after prolapse repair surgery, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly accepted pathophysiology when prolapse is involved is of the increased bladder outlet obstruction or resistance. This is supported when the correction of POP improves voiding function, which is associated with a reduction in OAB …”
Section: Introductionmentioning
confidence: 86%
“…DO is subdivided into idiopathic detrusor overactivity and neurogenic detrusor overactivity. The ICS 2002 report describes two types of DO: (1) phasic, which may or may not lead to urinary incontinence and (2) terminal, which is a single involuntary detrusor contraction that often results in complete bladder emptying. A presumptive diagnosis of OAB can be made with a careful history and physical examination.…”
mentioning
confidence: 99%
“…Placement in a patient with prolapse may relieve symptoms that may be secondary to poor emptying from outlet obstruction [33]. It is theorized that prolapse and chronic outlet obstruction lead to denervation of the bladder, thereby making the bladder supersensitive to acetylcholine.…”
Section: Vaginal Pessariesmentioning
confidence: 99%